The Nawawi al-Bantani's Hadith Thought in Tanqih al-Qaul al-Hatsits fi Syarh Lubab al-Hadits - 'Azima, Muhammad Fauzhan; Nur, Zunaidi (International Journal of Research, 2024)
Nawawi al-Bantani is known as a great scholar from Banten, on the west coast of Java who has expertise in various Islamic disciplines, including hadith science. This paper explores Nawawi al-Bantani's thoughts in the field of hadith science as contained in his book, namely the book Tanqih al-Qaul al-Hatsits fi Syarh Lubab al-Hadits. The book Tanqih al-Qaul is a book written by al-Bantani to lecture on the content of the book Lubab al-Hadits by as-Suyuthi. Although it is a type of syarah book, the book of Tanqih al-Qaul not only contains lectures on the hadiths in the book Lubab al-Hadits, but also contains al-Bantani's own thoughts as the author of the book Tanqih al-Qaul, in the field of hadith science. The research method used in this paper is a qualitative method with the type of library research. Meanwhile, as a data analysis knife, an analytical descriptive method is used with the type of analysis used, namely critical analysis. The results of the study show that the thinking of al-Bantani hadith is: the ability to use dha'if hadith in terms of fadhail al-a'mal and not in the field of law and creed, the importance of sanad for the validity of hadith narration, as well as the explanation of the definitions of basic terms in hadith science which include shahih, isnad, sanad, and matan. Al-Bantani's thinking in the field of hadith science also shows his independence from as-Suyuthi. This means that al-Bantani not only re-copied all the thoughts of as-Suyuthi in the book Lubab al-Hadits, but also gave rise to his own thoughts.